We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
215
1
avatar+4116 

#1 Help.

 Feb 7, 2018
 #1
avatar+101406 
+1

We can just solve the equations inside the parentheses

 

So we have

 

-9x + 5  =  3 + 4x    add 9x to both sides, subtract 3 from both sides

 

2 =  13x       divide both sides by  13

 

2/13  = x

 

 

f / g  =   [ 3x - 6 ] / [ x - 2]   =   3[ x - 2 ] / [ x - 2 ]  =  3

 

Note....that we can't put 2 into the original function because it makes the original denominator = 0

 

So.....second answer

 

 

cool cool cool

 Feb 7, 2018

22 Online Users

avatar
avatar
avatar